2005
DOI: 10.1073/pnas.0504021102
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B3 is a myelin-based inhibitor of neurite outgrowth

Abstract: The inability of CNS axons to regenerate after traumatic spinal cord injury is due, in part, to the inhibitory effects of myelin. The three major previously identified constituents of this activity (Nogo, myelin-associated glycoprotein, and oligodendrocyte myelin glycoprotein) were isolated based on their potent inhibition of axon outgrowth in vitro. All three myelin components transduce their inhibitory signals through the same Nogo receptor͞p75 neurotrophin receptor͞LINGO-1 (NgR1͞p75͞LINGO-1) complex. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
195
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(201 citation statements)
references
References 43 publications
4
195
1
1
Order By: Relevance
“…Members of this family are up-regulated following CNS injury (18,19). EphA4 has been implicated in the response to injury both as an astrocyte and as a neuronally expressed protein, but its functional role in recovery from neuronal injury is not clear (20)(21)(22)(23). Macrophage EphB3 has also been implicated in adult axon regeneration (24).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this family are up-regulated following CNS injury (18,19). EphA4 has been implicated in the response to injury both as an astrocyte and as a neuronally expressed protein, but its functional role in recovery from neuronal injury is not clear (20)(21)(22)(23). Macrophage EphB3 has also been implicated in adult axon regeneration (24).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…Of potential interest, ephrinB3 is known to be expressed by myelinating oligodendrocytes and to inhibit axonal extension (21). Additionally, ephrinB3 is known to function during development as a midline repellent for axons of the corticospinal tract in the spinal cord (17,25,26).…”
Section: Neurology | Locomotionmentioning
confidence: 99%
“…Among environmental mechanisms limiting CNS axonal growth are a number of myelin-associated proteins (1)(2)(3)(4)(5) and inhibitory proteoglcyans of the extracellular matrix (6)(7)(8). Modification of the CNS milieu enhances the sprouting or regeneration of several classes of axons (5,9,10).…”
mentioning
confidence: 99%
“…CST axons in either Ephrin-B3 or EphA4 mutant mice exhibit bilateral innervation of spinal grey matter due to the loss of the midline barrier (Ephrin-B3) or the receptor to sense the barrier (EphA4) (Dottori et al, 1998;Kullander et al, 2001;Yokoyama et al, 2001). Benson et al reported the expression of Ephrin-B3 in postnatal myelinating oligodendrocytes in the mouse spinal cord and provided evidence that this myelin component confers sensitivity to postnatal cortical neurons that express EphA4 (Benson et al, 2005). Moreover, in vitro neurite outgrowth studies demonstrated that a significant part of myelin inhibition is mediated by Ephrin-B3, which remarkably equals to the inhibitory activity of Nogo, MAG, and OMgp combined -at least for the postnatal cortical neurons tested (Benson et al, 2005).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%
“…Benson et al reported the expression of Ephrin-B3 in postnatal myelinating oligodendrocytes in the mouse spinal cord and provided evidence that this myelin component confers sensitivity to postnatal cortical neurons that express EphA4 (Benson et al, 2005). Moreover, in vitro neurite outgrowth studies demonstrated that a significant part of myelin inhibition is mediated by Ephrin-B3, which remarkably equals to the inhibitory activity of Nogo, MAG, and OMgp combined -at least for the postnatal cortical neurons tested (Benson et al, 2005). Interestingly, an independent group reported robust axonal regeneration and improved functional recovery in mice lacking EphA4, the receptor for Ephrin-B3 during CST development (Goldshmit et al, 2004).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%